Mild Hypobaric Hypoxia Enhances Post-exercise Vascular Responses in Young Male Runners - Saito, Yoko; Nakamura, Mariko; Eguchi, Kazumi; Otsuki, Takeshi (Frontiers in Physiology, 2019)
Sustained postexercise vasodilation has been hypothesized to be linked to exercise-induced angiogenesis. The purpose of the present study was to evaluate whether mild hypobaric hypoxia enhances postexercise reductions in systemic vascular resistance in young male runners. Seven male intercollegiate runners aged 19–21 years performed maximal incremental treadmill running with hypobaric hypoxia (corresponding to 2,200 m above sea level, hereinafter HH) and normobaric normoxia (corresponding to sea level, hereinafter NN). In addition, the third exercise test consisting of submaximal exercise with the same absolute exercise volume as during HH was performed under NN conditions (submaximal exercise with NN, hereinafter NNsubmax). Blood pressure and cardiac output (CO) were measured before and 15, 30, and 60 (p60) minutes after exercise. Compared with NN, exercise time was shorter with HH and NNsubmax (p<0.05). There were interactions between condition and systolic and mean blood pressure (SBP and MBP, respectively) changes after exercise: SBP and MBP were lower after exercise only with HH (p<0.05). No condition-related differences were found in CO. A condition × time interaction was identified in total peripheral resistance (TPR, the ratio of MBP to CO) (p<0.05). TPR was significantly lower after exercise compared to baseline under all conditions (p<0.05). However, the decrease in TPR was maintained longer with HH than with NN (p<0.05). TPR at p60 was still lower than baseline with HH (p<0.05), whereas TPR with NN and NNsubmax recovered to the baseline level at p60. Decreases in systemic vascular resistance after exercise were maintained longer under mild HH compared to NN despite lower exercise volume with HH.